2001
DOI: 10.1152/ajpendo.2001.280.6.e982
|View full text |Cite
|
Sign up to set email alerts
|

Postexercise nutrient intake timing in humans is critical to recovery of leg glucose and protein homeostasis

Abstract: Although the importance of postexercise nutrient ingestion timing has been investigated for glycogen metabolism, little is known about similar effects for protein dynamics. Each subject (n = 10) was studied twice, with the same oral supplement (10 g protein, 8 g carbohydrate, 3 g fat) being administered either immediately (EARLY) or 3 h (LATE) after 60 min of moderate-intensity exercise. Leg blood flow and circulating concentrations of glucose, amino acids, and insulin were similar for EARLY and LATE. Leg gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
140
2
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(157 citation statements)
references
References 42 publications
(54 reference statements)
8
140
2
3
Order By: Relevance
“…It is well-established in adults that the postexercise ingestion of protein is essential to maximize muscle protein synthesis (24,25,30) and increase whole body protein balance during the acute recovery period (23,25). The increase in muscle and whole body protein anabolism during this early (e.g., over 3 h) postexercise period facilitates the recovery process and can be sustained over 24 h (36,42).…”
mentioning
confidence: 99%
“…It is well-established in adults that the postexercise ingestion of protein is essential to maximize muscle protein synthesis (24,25,30) and increase whole body protein balance during the acute recovery period (23,25). The increase in muscle and whole body protein anabolism during this early (e.g., over 3 h) postexercise period facilitates the recovery process and can be sustained over 24 h (36,42).…”
mentioning
confidence: 99%
“…There are many studies on the combined effects of ingestion of protein or amino acids and timing of exercise, with many researchers reporting that ingestion of protein or amino acids directly after exercise is effective in muscle protein synthesis (12)(13)(14)(15). In addition, some studies on ingestion of proteins or amino acids prior to exercise have shown the ingestion to be effective in muscle protein synthesis (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…There is literature to support the benefits of complex protein consumption within 30 minutes of exercise for recovery [51,52]. A recent meta-analysis supports consuming adequate protein in combination with resistance exercise as the key factors for maximizing muscle protein accretion [53].…”
Section: Recommended Dietary Allowancementioning
confidence: 99%